Juridical Review of KPU Regulation Number 10 of 2023 on Women's Representation in Parliament - Sari, Indah Permata; Melayu, Hasnul Arifin; Usman, Bustamam (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2024)
Women's representation in Indonesian politics is part of the journey of democracy and the protection of minority interests. The KPU, as the institution responsible for organizing elections, some time ago the KPU issued a new regulation on women's representation contained in PKPU No. 10 of 2023 concerning Women's Representation, which regulates the mechanism for rounding fractional numbers so that it can reduce women's representation if the calculation results are less than 50%. This is contrary to the Election Law, which requires at least 30% female representation. This KPU regulation creates uncertainty and the potential for a reduction in the number of women, which can be detrimental to women's rights. This study analyzes the position of PKPU No. 10 of 2023 concerning Law No. 7 of 2017 and the perspective of siyasah dusturiyah; Regulations made by the authorized institutions emphasize that lower regulations must be subject to higher regulations and must prioritize the interests of the people. This article is based on articles and regulations governing women's representation. This research is qualitative research with a normative juridical approach, to facilitate data search as literature research through laws, journals, legal dictionaries, and others. As a result of this study, it can be concluded that PKPU No. 10 of 2023 is contrary to Law No. 7 of 2017 and should be revoked to ensure that women's rights are fulfilled under the principles of justice and equality in politics.